Pomegranate peel extract protects against the development of diabetic cardiomyopathy in rats by inhibiting pyroptosis and downregulating LncRNA-MALAT1 - Abo-Saif, Mariam Ali; Ragab, Amany E.; Ibrahim, Amera O.; Abdelzaher, Othman F.; Mehanyd, Ahmed B. M.; Saber-Ayad, Maha; El-Feky, Ola A. (Frontiers in Pharmacology, 2023)
Background: Pyroptosis is an inflammatory programmed cell death accompanied by activation of inflammasomes and maturation of pro-inflammatory cytokines interleukin-1β (IL-1β) and IL-18. Pytoptosis is closely linked to the development of diabetic cardiomyopathy (DC). Pomegranate peel extract (PPE) exhibits a cardioprotective effect due to its antioxidant and anti-inflammatory properties. This study aimed to investigate the protective effect of PPE on the myocardium in a rat model of DC, and to determine the underlying molecular mechanism. Methods: Type1 diabetes was induced in the rats by intraperitoneal injection of streptozotocin. The rats in the treated groups received (150 mg/kg) PPE orally and daily for 8 weeks. The effects on the survival rate, lipid profile, serum cardiac troponin-1, lipid peroxidation and tissue fibrosis were assessed. Additionally, the expression of pyroptosis-related gene (NLRP3 and caspase-1) and lncRNA-MALAT1 in the heart tissue was determined. The PPE was analyzed using UPLC-MS/MS and NMR for characterizing the phytochemical content. Results: Prophylactic treatment with PPE significantly ameliorated cardiac hypertrophy in the diabetic rats and increased the survival rate. Moreover, prophylactic treatment with PPE in the diabetic rats significantly improved the lipid profile, decreased serum cardiac troponin-1, and decreased lipid peroxidation in the myocardial tissue. Histopathological examination of the cardiac tissues showed a marked reductiondecrease in fibrosis (decrease in collagen volume and number of TGF-β positive cells) as well as preservation of normal myocardial structures in the diabetic rats treated with PPE. There was a significant decrease in the expression of pyroptosis-related gene (NLRP3 and caspase-1) and lncRNA-MALAT1 in the heart tissue of the diabetic rats treated with PPE. In addition, the concentration of IL-1β and caspase-1 significantly decreased in the heart tissue of the same group. The protective effect of the PPE on diabetic cardiomyopathy could be due to inhibition of pyroptosis and down-regulation of lncRNA-MALAT1. The phytochemical analysis of the PPE indicated that major compounds were hexahydroxydiphenic acid glucoside, caffeoyl quinic acid, gluconic acid, citric acid, gallic and punicalagin. Conclusion: The PPE exhibited a cardioprotective potential in diabetic rats owing to its unique antioxidant, anti-inflammatory, and antifibrotic properties as well as its ability to improve the lipid profile.